A COMPARATIVE STUDY OF KINDERGARTEN STUDENTS’ LEVELS OF ENGLISH ACHIEVEMENT BY WAY OF TRACKING AND DETRACKING AT CHOKCHAI HATHAIRAJ SCHOOL IN BANGKOK, THAILAND - FOX, ADAM DONALD; EAMORAPHAN, SUWATTANA (Scholar: Human Sciences, 2022)
The purpose of this study was to compare Kindergarten students’ levels of English achievement by way of two different grouping arrangements known as tracking and detracking at Chokchai Hathairaj School in, Bangkok, Thailand. This study was to determine if any statistically significant difference existed between those instructed in accordance with tracking and those instructed in accordance with detracking in terms of their respected levels of English achievement. This study was conducted over a period of nine weeks from July 2020 to August 2020. A total of 60 Kindergarten students took part in this study. In this study, 30 students were grouped according to ability as determined by a pre-test and in accordance with tracking and 30 students were grouped randomly regardless of ability in accordance with detracking. This study used a pre-test and a post-test to identify students’ levels of English achievement. The test scores were analyzed by of statistical analysis including mean and standard deviation and compared by way of paired samples and independent samples t-tests The findings showed there was a significant difference between pre-test and post-tests by ways of both tracking and detracking at the .05 level. The findings also showed no significant difference existed in gain difference between pre-tests and post-tests by way of tracking and detracking at the .05 level.